EFFECT OF ACUPRESSURE ON QUALITY OF SLEEP AND PULSE RATE IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Eko Rustamaji Wiyatno; Rr. Sri Endang Pujiastuti; Titin Suheri; Djenta Saha (Belitung Nursing Journal, 2017)
Background: Patients with acute myocardial infarction have a change in sleep pattern. Acupressure is identified as a therapy with the principle of healing to deal with sleep changes. Objective: To analyze the effect of acupressure on sleep quality and pulse rate in patients with acute myocardial infarction. Methods: This study employed a quasi-experiment study with non-randomized pretest-posttest with control group design. There were 50 respondents selected in this study, with 25 assigned in the intervention and control group using consecutive sampling. Quality Sleep Questionnaire and bedside monitor were used to measure sleep quality and pulse rate. Acupressure in combination of Neiguan point (PC 6), Shenmen (HT7), Sanyinjiao (SP6), Yintang (EX3) and Tay (EX5) was given as the nursing intervention in this study. Data were analyzed using paired t-test and independent t-test. Results: There was statistically a significant increase of quality of sleep and significant decrease of pulse rate in the intervention group with p-value 0.000 (<0.05). Conclusion: Acupressure has a significant effect on the increase of sleep quality and the decrease of pulse rate in patients with acute myocardial infarction. Thus, it is suggested that acupressure could be one of the nursing interventions for AMI patients to increase sleep quality and decrease of pulse rate.